Features of Strategic Alliances in the Global Economy - Samadovich, Saidov Mashal; Zarnigor, Vafoeva (American Journal of Economics and Business Management, 2023)
This article developed the improvement of strategic alliances and global competition in the modern economy; strategic alliances of the Uztekstilprom association were identified. The activities of the association "Uztekstilprom" were analyzed, practical proposals were developed to improve the way to improve strategic alliances in the association "Uztekstilprom".